Paragraph Writing Instructional Material: Students’ Need Analysis - Ngasbun Egar; Siti Musarokah; Fitri Yulianti (Soegijapranata Catholic University, 2025)
This study explores paragraph writing instructional materials based on students’ needs analysis in an English as a Foreign Language (EFL) context. The purpose of this study is to identify students’ learning needs and perceptions of existing paragraph writing materials, particularly in developing Major Supporting Sentences (MASS) and Minor Supporting Sentences (MISS). Data were collected through questionnaires and semi-structured interviews to capture both quantitative and qualitative perspectives on students’ learning experiences. The quantitative data were analyzed using SPSS version 29, while the qualitative interview data were examined using NVivo version 11 to identify emerging themes related to students’ instructional needs. The findings reveal that students perceive the instructional materials as generally effective in providing clear explanations and structured exercises to support paragraph writing. However, the needs analysis also indicates several areas requiring improvement, including the limited variety of examples, insufficient practical writing exercises, and the lack of supplementary learning resources such as multimedia tools. These unmet needs suggest that the current materials do not fully accommodate students’ diverse learning preferences. The study concludes that needs-based refinement of paragraph writing instructional materials that is by incorporating more interactive elements, authentic examples, and additional learning supports can enhance EFL students’ paragraph writing competence and overall language development